2016
DOI: 10.1530/eje-15-0515
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary hypophosphatemia in Norway: a retrospective population-based study of genotypes, phenotypes, and treatment complications

Abstract: ObjectiveHereditary hypophosphatemias (HH) are rare monogenic conditions characterized by decreased renal tubular phosphate reabsorption. The aim of this study was to explore the prevalence, genotypes, phenotypic spectrum, treatment response, and complications of treatment in the Norwegian population of children with HH.DesignRetrospective national cohort study.MethodsSanger sequencing and multiplex ligand-dependent probe amplification analysis of PHEX and Sanger sequencing of FGF23, DMP1, ENPP1KL, and FAM20C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 77 publications
10
112
2
Order By: Relevance
“…These events, as well as nephrocalcinosis, are known risks associated with conventional therapy. (2,24) In contrast, in the present study, we observed no changes in serum calcium or PTH concentrations, urine calcium excretion, nor renal nephrocalcinosis scores and no incidents of hyperphosphatemia. Burosumab's safety profile was similar to that seen in previous clinical trials, with most adverse events being mild to moderate in severity.…”
Section: Journal Of Bone and Mineral Researchcontrasting
confidence: 96%
See 1 more Smart Citation
“…These events, as well as nephrocalcinosis, are known risks associated with conventional therapy. (2,24) In contrast, in the present study, we observed no changes in serum calcium or PTH concentrations, urine calcium excretion, nor renal nephrocalcinosis scores and no incidents of hyperphosphatemia. Burosumab's safety profile was similar to that seen in previous clinical trials, with most adverse events being mild to moderate in severity.…”
Section: Journal Of Bone and Mineral Researchcontrasting
confidence: 96%
“…Sullivan and colleagues reported hypercalciuria and tertiary hyperparathyroidism. These events, as well as nephrocalcinosis, are known risks associated with conventional therapy . In contrast, in the present study, we observed no changes in serum calcium or PTH concentrations, urine calcium excretion, nor renal nephrocalcinosis scores and no incidents of hyperphosphatemia.…”
Section: Discussionsupporting
confidence: 69%
“…Several other vitamin D analogues are also available 62,117,121,122 . As in healthy children, 25 reported in 30-70% of patients with XLH 3,48,56,87,[96][97][98][99]118 . Several reports suggest positive associations between daily oral phosphate doses and the risk of developing nephrocalcinosis, whereas the relationship with active vitamin D therapy and/or with the presence of hypercalciuria has been observed less frequently 3,48,96,97,99,118,125 .…”
Section: Active and Native Vitamin Dmentioning
confidence: 87%
“…X‐linked hypophosphatemia (XLH, OMIM #307800), the most common genetic rickets or osteomalacia, is due to loss‐of‐function mutations of PHEX : “phosphate‐regulating endopeptidase homolog, X‐linked” . Consequently, circulating levels of the phosphatonin fibroblast growth factor 23 (FGF23) increase and affected individuals manifest hypophosphatemia from renal wasting of inorganic phosphate (Pi), diminished kidney synthesis of 1,25‐dihydroxyvitamin D (1,25(OH) 2 D), and decreased intestinal absorption of calcium (Ca) and Pi . XLH accounts for >80% of heritable hypophosphatemic bone disease and occurs in ~1 per 20,000 births .…”
Section: Introductionmentioning
confidence: 99%
“…Its 22 exons encode a 749–amino acid enzyme that, when compromised, increases circulating FGF23 thereby diminishing expression of two sodium‐Pi cotransporters in renal proximal tubule cells . Furthermore, FGF23 downregulates kidney 1α‐hydroxylase necessary to activate 25‐hydroxyvitamin D to 1,25(OH) 2 D . For decades, conventional medical therapy for XLH has been one or two daily oral doses of bioactive vitamin D 3 (1,25(OH) 2 D 3 or 1α‐hydroxyvitamin D 3 ) with multiple daily oral doses of a Pi salt, at least until linear growth is complete .…”
Section: Introductionmentioning
confidence: 99%